TP1-10 Non tumour brain biopsies in alder hey paediatric neurosurgery. Issue 3 (14th February 2019) - Tonder, LV; Foster, M; Hennigan, D; Kneen, R; Iyer, A; Parks, C; Burn, S; Mallucci, C
Abstract : Objectives: To review the utility of non-tumour brain biopsies in Alder Hey Children's NHS Foundation Trust Paediatric Neurosurgery Department. Methods: Operative records were searched for 'biopsy'. Case notes were reviewed for referral source, histology, surgical complication and outcome. Tumour, epilepsy and non-brain biopsy cases were excluded. Results: 83 'biopsy' cases were identified between 2008 and 2017. 31 tumour, 5 epilepsy, 2 infections and 28 non brain/other biopsies were excluded. 17 brain biopsies for non-tumour causes were seen. 15 patients were referred by neurology, 2 by rheumatology. 14 underwent a craniotomy/mini-craniotomy, 3 had burrholes.4 biopsies were non diagnostic, 2 were abnormal but inconclusive for diagnosis. Diagnoses included: 3 demyelinating lesions, 2 normal brain tissue, 1 neurosarcoidosis, 1 autoimmune encephalitis, 1 definite Rasmussen's Encephalitis, 1 possible Rasmussen's Encephalitis, 1 systemic lupus erythematosus associated CNS vasculitis, 1 inflammatory infiltrate (secondary to hydrocephalus/ventriculitis), 1 patient developed a late wound infection. No other surgical morbidities/mortalities were recorded. 11 of these cases had a change in management or the treating team were reassured due to the result of the biopsy (i.e. were able to start immunomodulatory drugs in the absence of infection). Conclusions: 65% of brain biopsies were diagnostic. 71% of biopsies either changed management or reassured the treating team about a line of management. The procedure is low risk with 0.06% morbidity and 0% mortality.